Organic Material Addition Optimizes Soil Structure by Enhancing Copiotrophic Bacterial Abundances of Nitrogen Cycling Microorganisms in Northeast China - Yang Yue; Xiangwei Gong; Yongzhao Zheng; Ping Tian; Ying Jiang; Hongyu Zhang; Hua Qi (Agronomy, 2023)
Using organic fertilizer and maize straw as friendly amendment measures is effective for altering soil nitrogen (N) cycling in farmlands. However, the synthetical effects of organic fertilizer combined with straw returning on soil quality remain unknown, especially in response to soil nitrification and denitrification microorganisms. We set up an experiment in brunisolic soil from Northeast China, mainly including four treatments: CK (no addition without traditional chemical fertilizer), O (organic fertilizer application), S (straw returning), and OS (organic fertilizer combined with straw returning). The soil nitrification and denitrification microorganisms were further investigated using high-throughput sequencing. Our results show that, compared to CK, the soil water content, field capacity, macroaggregates with a diameter > 0.25 mm, mean weight diameter, total carbon, total nitrogen, ammonium, nitrate, microbial biomass carbon, and microbial biomass nitrogen were significantly improved, and penetration resistance was reduced in a 0–20 cm soil layer under O, S, and OS treatments. Moreover, OS treatment effectively increased the available potassium and available phosphorus content and decreased the three-phase R-value. The application of organic fertilizer and straw effectively optimized the soil structure, especially the OS treatment. Compared to CK, O, S, and OS treatments had a higher abundance of ammonia-oxidizing archaea (AOA) and further enhanced the alpha diversity and lower abundance of ammonia-oxidizing bacteria (AOB) and nirK-, nirS-, and nosZ-type denitrifying microbes. AOA and nirK were the key drivers of the ammonia oxidation process and nitrite reduction process, respectively. Meanwhile, the application of organic fertilizer and straw regulated the relative abundance of Nitrososphaeria (AOA), Gammaproteobacteria (nirK and nirS), Alphaproteobacteria (nirK), and Betaproteobacteria (nirS) in the soil. Organic fertilizer and straw returning regulated the soil structure by enhancing the abundance of Alphaproteobacteria, Betaproteobacteria, and Gammaproteobacteria in the nitrifying and denitrifying microorganism communities. Taken together, OS treatment was a suitable straw-returning practice for optimizing the nutrient balance of the farmland ecosystem in Northeast China. However, this study did not determine how to reduce traditional nitrogen fertilizer applications under organic fertilizer application and straw returning; therefore, we aim to carry out related research in future works.